2019
DOI: 10.1016/j.rmed.2019.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary associations of health status in severe asthma and bronchiectasis: Comorbidities and functional outcomes

Abstract: Tertiles of high-sensitivity C-reactive protein Sarcopenia absent vs. present Tertiles of steps/day Tertiles of isometric leg strength

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Asthma is a complex heterogenous disease in which individual variability in clinical presentation, disease severity and therapeutic response is common 1,2 . To add to this complexity, behaviours/risk-factors and extrapulmonary comorbidities, also referred to as "Treatable Traits", that are associated with adverse clinical outcomes are common in asthma [3][4][5] . Physical inactivity is one proposed Treatable Trait that is recognised as an important modifiable risk-factor for impaired respiratory functioning, asthma control, quality of life (QoL) and mental health, increased disease severity and exacerbation risk, and ultimately increased healthcare use 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a complex heterogenous disease in which individual variability in clinical presentation, disease severity and therapeutic response is common 1,2 . To add to this complexity, behaviours/risk-factors and extrapulmonary comorbidities, also referred to as "Treatable Traits", that are associated with adverse clinical outcomes are common in asthma [3][4][5] . Physical inactivity is one proposed Treatable Trait that is recognised as an important modifiable risk-factor for impaired respiratory functioning, asthma control, quality of life (QoL) and mental health, increased disease severity and exacerbation risk, and ultimately increased healthcare use 6 .…”
Section: Introductionmentioning
confidence: 99%
“…6 10 For instance, asthma patients with obesity demonstrated high levels of serum C reactive protein, representing a systemic inflammatory response. 37 Similarly, these inflammatory conditions could influence inner ear inflammation and SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…This systemic inflammation might be linked to extrapulmonary disorders, including cardiovascular and metabolic diseases 6 10. For instance, asthma patients with obesity demonstrated high levels of serum C reactive protein, representing a systemic inflammatory response 37. Similarly, these inflammatory conditions could influence inner ear inflammation and SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…To add to this complexity, there are a number of extrapulmonary comorbidities and risk factors, or "traits" that independently affect future asthma outcomes (9)(10)(11). This highlights the importance of individualized asthma management strategies that look beyond the pulmonary system.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the importance of individualized asthma management strategies that look beyond the pulmonary system. In severe asthma, it has been demonstrated that physical inactivity, symptoms of anxiety and depression, greater systemic inflammation and lower isometric leg strength are independently associated with greater health-related quality of life (HRQoL) impairment ( 9 ). While in another analysis, of the 10 predictors of future exacerbation risk identified in severe asthma, eight were extrapulmonary traits; depression, anxiety, obstructive sleep apnea (OSA), vocal cord dysfunction (VCD), upper airway disease, systemic inflammation, underweight, and inhaler device polypharmacy ( 10 ).…”
Section: Introductionmentioning
confidence: 99%